Efforts to Improve Knowledge in Formulating Nursing Diagnoses through Mini Seminar Training - Somantri, Irman; Ibrahim, Kusman; Mediawati, Ati Surya; Ramoo, Vimala; Yudianto, Kurniawan (Media Karya Kesehatan, 2025)
Nursing professional organizations in Indonesia have established standardized guidelines for nursing documentation. However, the formulation of nursing diagnoses is still carried out as a routine activity by nursing teams, resulting in cases where diagnoses are not established according to proper standards. This community service program aimed to improve nurses’ understanding of nursing diagnosis formulation in accordance with Indonesian standards. The activity was implemented using a mini-seminar method involving 30 participants from two hospitals in the Bandung area. It was part of an activity based on Kemmis and McTaggart’s theory. In the preliminary phase, evaluation was conducted using a knowledge scale measurement and documentation observation to assess the number of nursing diagnoses implemented. The results showed an improvement in nurses’ ability to formulate nursing diagnoses, marked by an increase in understanding from only 10% before the activity to 83.33% after, with a p-value <0.001. In addition, the average number of nursing diagnosis labels increased from two to five per nurse. These findings indicate that the mini-seminar method is effective in enhancing nurses’ ability to formulate nursing diagnoses in accordance with established standards. Keywords: Nursing diagnosis, partisipatory research.